E0419 The applying of aspiration catheter in revascularisation in patients with ST-elevation myocardial infarction. (17th November 2010) - Weiming, Li; Yawei, Xu; Ke, Wang; Yangqing, Chen; Yidong, Wei; Yuanmin, Li; Wenliang, Che; Lei, Hou; Yunlan, Lu
Abstract : Objectives: To observe the immediate and recent treatment effects of applying the aspiration catheter in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Methods: From March to June 2010, we enrolled the STEMI patients presenting with TIMI Flow Grade 0 or 1 in the infarct related artery (IRA) at baseline CAG undergoing primary PCI. The aspiration catheter (Medtronic Inc., Export?) was applied immediately to aspirate the intracoronary thrombus. Whether predilatating and/or stenting were decided by the blood flow and the condition of lesions. The patients from October 2009 to February 2010 who was diagnosed as STEMI and received non-aspiration were enrolled as control group. The immediate and recent clinical outcomes of applying the aspiration catheter were compared between the two groups. Results: There were 25 cases in Group thrombus-aspiration (2 cases of subacute stent thrombosis). After having aspirated the intracoronary thrombus using the aspiration catheter, 14 cases of STEMI recovered immediately (9 cases received direct stenting; 3 cases implanted stents after balloon predilatation, and had satisfied results; 2 cases of subacute stent thrombosis received the antithrombotic therapy, included intravenous infusion of Xinweining for 36 h in CCU immediately after recovering TIMI grade-3 flow). 10 cases recovered TIMI 1-2, 1 cases also showed no-reflow. All of the 11 cases received the balloon predilatation and stenting, only one showed slow flow, the others recovered. There was no other severe complication during and after the operation. There was no in-stent thrombosis during 1 month follow-up, and the cardiac function improved largely. There were 22 cases in Group non-aspiration, 4 cases received direct stenting, 18 cases received balloon predilatation and stenting.5 cases showed slow flow, 3 cases recovered normal flow after intra-coronary infusion of nitroglycerin, verapamil and Xinweinin, but 2 cases also showed TIMI 1, and accompanied heart failure. Conclusions: The applying of aspiration catheter in patients with STEMI prior to primary PCI could increase the opportunities of direct stenting, improve myocardial reperfusion, immediate and recent clinical outcomes as compared with PCI in the absence of thrombus aspiration, and also show ease and safe procedure.